PENGARUH PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KEMAMPUAN MENULIS CERITA RAKYAT - Olivia Salsa; Nur Amalia (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
The Influence of the Application of the Project Based Learning Model on the Ability to Write Folklore. The purpose of this study was to describe the effect of the Project Based Learning model on writing folklore in class X SMAN 7 Depok. This type of research is quantitative, and the experimental method used is a two-group static design that is pre-experimental. The data source used was the class X students of SMAN 7 Depok. Data collection was carried out through tests, questionnaires, and observations. The data analysis technique is carried out through inferential statistics and categorization. Based on the results of the analysis, it is known that: first, the students' folklore writing skills using the Project Based Learning model are in good condition (84.29). Second, students' folklore writing skills through the non-project-based learning model are less qualified (69.66). Third, based on the results of the t-test there is an influence of the Project Based Learning model on the ability to write folklore in class X SMAN 7 Depok.